Pengaruh Store Atmosphere , Harga Dan Kelengkapan Produk Terhadap Keputusan Pembelian Pelanggan Pada Budiman Swalayan Kota Padang (Studi Kasus Mahasiswa Feb Universitas Dharma Andalas) - Muni Ayu Lestari; Heru Aulia Azman (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This re$se$arch analyze$s the$ influe$nce$ of store$ atmosphe$re$, price$ and product comple$te$ne$ss on custome$r purchasing de$cisions at Budiman supe$rmarke$ts in Padang City (case$ study of FE$B stude$nts at Dharma Andalas Unive$rsity) using quantitative$ me$thods. This re$se$arch aims to de$te$rmine$ the$ influe$nce$ of store$ atmosphe$re$, price$ and product comple$te$ne$ss on custome$r purchasing de$cisions at Budiman Supe$rmarke$ts in Padang City. This re$se$arch use$s data colle$ction te$chnique$s in the$ form of que$stionnaire$s with a quantitative$ approach, whe$re$ data is colle$cte$d from 123 re$sponde$nts who are$ FE$B stude$nts at Dharma Andalas Unive$rsity. The$ population of this re$se$arch was 1,062 FE$B stude$nts at Dharma Andalas Unive$rsity. And sampling in this study use$d the$ rao soft size$ calculator software$ me$thod to calculate$ the$ numbe$r of sample$s, so the$ sample$ in this study was 123 FE$B stude$nts at Dharma Andalas Unive$rsity. Data colle$ction was carrie$d out through que$stionnaire$s distribute$d to 123 re$sponde$nts, which we$re$ the$n analyze$d using SPSS (Statistical Product and Se$rvice$ Solutions) software$ ve$rsion 21. The$ re$se$arch re$sults show that: store$ atmosphe$re$ has a positive$ and significant influe$nce$ on custome$r purchasing de$cisions at Budiman Swalayan Padang City, price$ has a positive$ and significant influe$nce$ on custome$r purchasing de$cisions at Budiman Swalayan Padang City, and product comple$te$ne$ss has a positive$ and significant influe$nce$ on custome$r purchasing de$cisions at Budiman Swalayan Padang City, store$ atmosphe$re$, price$ and product comple$te$ne$ss simultane$ously have$ a positive$ and significant influe$nce$ on custome$r purchasing de$cisions at Budiman Swalayan Padang City.